Experiences of nursing professionals in alternative and complementing therapies applied to people in pain situations (2010)
To know the experiences of nursing professionals on the use of alternative and complementing therapies applied during health care to people in pain situations, a qualitative study was carried out, as a graduation project for a group of nursing students –undergraduates– from the Universidad del Bosque, between 2005 and 2007, in which four nursing professionals took part. They had several years of experience in the use of floral therapy, acupuncture, homeopathy, chiropractic massage therapy and naturopathy; in other words, those therapies that also enable a synergic action when combined with the conventional therapeutic medical-pharmacologic-surgical procedures, which they complement; the selection of participants wasmadeusing the "snow ball" technique. The information was gathered by means of semi-structured deep interviews. The analysis of the results enabled us to learn that said experiences do not have as sole purpose to relieve a determined type of pain, but, generally, to evaluate the health condition and to intervene with an integral focus, considering the individual as a holistic human being; on the other hand, this work has given the students great satisfaction and possibilities for personal development.